Cyanobacteria blooms and cyanotoxin occurrence in the Guadiana (SE - Portugal): preliminary results - Caetano, Sandra (2012)
Cyanobacteria are a recognised public health hazard, because the majority of species is able to produce toxins. The monitoring is usually restricted to freshwater environments, like lakes or dams used for water supply. Cyanobacteria blooms have been regularly reported in the Guadiana River and high estuary and most of the observed cyanobacteria were toxin producers.